KETIDAKEFEKTIFAN KALIMAT DALAM TEKS LAPORAN HASIL OBSERVASI SISWA KELAS VII SMP NEGERI 2 KOTO XI TARUSAN - Fitriani, Silpia; Emidar, Emidar (Universitas Negeri Padang, 2019)
ABSTRACTÂ This research was conducted to describe the ineffectiveness of sentences in the text of the report on the observation of seventh grade students of State Middle School 2 Koto XI Tarusan based on sentence structure. to describe the ineffectiveness of sentences in the report text of the observation of class VII students of State Middle School 2 Koto XI Tarusan based on word choice. to describe the ineffectiveness of the sentence in the text of the report on the observations of class VII students of SMP Negeri 2 Koto XI Tarusan based on the spelling used (EBI). This type of research is qualitative with descriptive method. The data of this study are the sentences contained in the text of student observation reports. Data were analyzed by steps, namely (1) researchers investigating data sources, (2) investigating effective sentences, (3) analyzing collected data based on indicators of effective sentence assessment, (4) data analysis results examined by triangulation informants, (5 ) draw a conclusion. Based on the sentence obtained from 30 text reports on student observations. The researcher found that 182 sentences contained 115 ineffective sentences and 67 effective sentences. The ineffectiveness of the sentence caused by the sentence structure of 31 sentences. The ineffectiveness of the sentence is caused by the choice of 73 sentences. The ineffectiveness of the sentence caused by 88 sentences of using the EBI spelling.Â Kata Kunci: Ketidakefektifan Kalimat, Teks Laporan Hasil Observasi